Formulation and evaluation of antibacterial nanoemulsion mouthwash from active fraction of lemongrass stem (Cymbopogon Nardus) - Weri Veranita; Desy Ayu Irma Permatasari (Proceeding of International Conference on Science, Health, And Technology, 2022)
Currently, the use of pharmaceutical preparations based on natural ingredients has begun to be in great demand by the public. This is because the use of synthetic drugs has weaknesses such as being able to cause resistance. Dental caries is one of the most common oral diseases in humans. One of the plants that has the potential to be used as an antibacterial in the oral cavity is Lemongrass (Cymbopogon Nardus L.). The use of emulsion mouthwash in the oral cavity is one of the treatments that is still being carried out. Mouthwash with nano size has advantages such as being able to enter the body more easily. This study aims to determine the physical properties of mouthwash nanoemulsion ethyl acetate extract of Serai Wangi (Cymbopogon Nardus L.) by evaluating the preparation. The nanoemulsion mouthwash was made with the composition of Palm Oil as the oil phase, 96% ethanol as the cosurfactant, Tween 80 as the surfactant, and phosphate buffer pH 6 as the water phase. Then the mixture was stirred at a speed of 1000 rpm and sonicated and then tested for evaluation of the preparation including pH test, homogeneity test, organoleptic test, centrifugation test and transmittance test using UV-Vis Spectrophotometer. The results of the analysis of the entire nanoemulsion formula showed that the more the mangosteen rind extract was incorporated into the oil phase, the more concentrated the color of the nanoemulsion formed and the smaller the percentage of transmittance produced.